Short Report: The Moisture Balance with Aloe Vera Gel in Diabetic Wound Healing - Fahrianto Selamet; Andi Mayasari Usman; Rian Adi Pamungkas (Alta Dharma Publisher, 2018)
Diabetic foot ulcer (DF) is a chronic complication of diabetes mellitus (DM), which impact on the morbidity, mortality and quality of patients’ lives.Of those patients with diabetes mellitus, approximately 15% to 25% developed to the foot ulcer. Beside has the infection and debridement of devitalized tissue downloading; the moisture imbalance becomes the factors of recalcitrant to healing. Moist wound healing is often contraindicated to the non-healable wounds. While wound care involves the debridement, bacterial reduction, and moisture balance in order to achieve the good granulation of the tissue development and adequate blood supply.